2017
DOI: 10.1037/adb0000251
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the slot machine zone with attentional dual tasks and respiratory sinus arrhythmia.

Abstract: Recent accounts of problematic electronic gaming machine (EGM) gambling have suggested attentional pathology among at-risk players. A putative slot machine zone is characterized by an intense immersion during game play, causing a neglect of outside events and competing goals. Prior studies of EGM immersion have relied heavily upon retrospective self-report scales. Here, the authors attempt to identify behavioral and psychophysiological correlates of the immersion experience. In samples of undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…Immersion is a feeling of intense focus on a particular activity that reduces attention to competing goals and stimuli. Although viewed as desirable in many occupational and recreational contexts , immersion in gambling activities is a robust predictor of problem gambling risk . Slot machine gambling may be especially immersive: an Australian survey found that 79% of gambling‐related immersion experiences involved slot machines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immersion is a feeling of intense focus on a particular activity that reduces attention to competing goals and stimuli. Although viewed as desirable in many occupational and recreational contexts , immersion in gambling activities is a robust predictor of problem gambling risk . Slot machine gambling may be especially immersive: an Australian survey found that 79% of gambling‐related immersion experiences involved slot machines .…”
Section: Introductionmentioning
confidence: 99%
“…Most research on slot machine immersion has employed self‐report measures, but a few behavioural studies have tested whether immersed gamblers were less responsive to stimuli outside the game . Crucially, this ‘dual task’ approach cannot assess the allocation of attentional resources to the game itself.…”
Section: Introductionmentioning
confidence: 99%
“…Low heart rate variability is widely treated as a marker of impaired emotional regulation (Holzman & Bridgett, 2017) and has been widely reported in clinical groups with substance use disorders (Crowell et al, 2017;Quintana et al, 2013). Our hypothesis for RSA was also informed by an earlier study, in which regular slot machine gamblers with varying levels of disordered gambling showed lower RSA than a student group of novice gamblers (Murch et al, 2017), although the groups were not demographically comparable in that study. A physiological marker of deficient emotion regulation could have utility in treatment contexts given the potential for unobtrusive and arms-length monitoring and would concur with other studies employing cognitive and self-report measures of emotion regulation in gambling disorder Williams et al, 2012).…”
Section: Model 1: Smoking Status (All Participants)mentioning
confidence: 92%
“…In a previous study measuring RSA in a group of students and a group of regular slot machine gamblers, resting RSA was noted to be markedly lower in the regular gamblers, who displayed moderate levels of disordered gambling. However, the two groups in that study were not intended to be demographically balanced (Murch, Chu, & Clark, ). In the present study, we predicted that resting state RSA would be reduced in a group of individuals with gambling disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Button press data was recorded with and extracted from AcqKnowledge ® 4.4 (Biopac Systems Ltd., Goleta, CA). To mitigate the recording of accidental presses or of button pressing in excess of actual betting, button press events were not considered if they occurred within .5 seconds from the previous press (Murch, Chu, & Clark, 2017). Video recordings of the gambling sessions were also taken in order to have a transcript for examining atypical button pressing patterns (e.g., rapid button pressing or long breaks in gambling) 2.4 Procedure…”
Section: Play Behaviour During the Gambling Sessionmentioning
confidence: 99%